A full-scale physical model test apparatus for investigating the dynamic performance of the slab track system of a high-speed railway. (February 2016) - Bian, Xuecheng; Jiang, Hongguang; Chen, Yunmin; Jiang, Jianqun; Han, Jie
This study involves the development of a full-scale physical model test apparatus to investigate the dynamic performance of the slab track system of a high-speed railway. A portion of a railway ballastless track with embankment and underlying soil strata was built inside a steel box (15 m long, 5 m wide and 6 m high). A sequential-load-generating system consisting of eight high-performance actuators was developed to apply a load that was equivalent to that generated by a train moving at speeds up to 360 km/h. Two loading conditions can be implemented in the tests, a stationary cyclic loading (using one actuator) or a simulated moving train loading (using all eight actuators). Three test cases were performed to demonstrate the capacity of the proposed test facility. The first case was to test the load-sharing ratio of fasteners beneath the rails to determine the load distribution on the track slab. A formula, based on the test results, was proposed to determine the transfer process of the loads between the train wheel and the rail fasteners. The second case was a stationary cyclic loading test, which applied loads with varying frequencies to the rails using a single actuator. The resonance frequency of the track/embankment/soil system was determined in these tests to be about 16 Hz, which coincided with theoretically computed results and field measurements. The final case was to simulate the dynamic excitation resulting from the passage of a train on the track at various speeds (up to 360 km/h). The test results on track vibrations in the physical model test showed reasonably good agreement with field measurements. These three test cases fully demonstrate the ability of the newly developed full-scale test facility to simulate dynamic excitation from trains and its ability to explore the dynamic performance of railway structures under train loadings.